Pengaruh Pemberian Makanan Tambahan Kacang Hijau dan Ikan Lele terhadap Berat Badan Balita Underweight - DANIA SAFA'ATIN AINI; WIDIA SHOFA ILMIAH; ANIK SRI PURWANTI (Hang Tuah Medical Journal, 2026)
Underweight in children aged 1–5 years can hinder growth and development. Children with a weight-for-age Z-score (WAZ) < -2 SD are classified as underweight by WHO and require nutritional intervention. Supplementary feeding (PMT) based on local food with high protein and energy content can improve nutritional status. This quasi-experimental study employed a pretest–posttest control group design involving 32 children at Posyandu Balai Desa Sumberagung, divided into 16 intervention and 16 control participants. The intervention group received PMT made from mung bean and catfish for 30 days, while the control group received routine Posyandu services. Researchers did not directly observe children consuming PMT but relied on parental reports. Body weight was measured before and after the intervention and analyzed using Paired Sample T-Test and Independent Sample T-Test (α=0.05). Results showed the mean WAZ of the intervention group increased from -2.47 to -1.85 (p=0.000), whereas the control group increased from -2.46 to -2.33 (p=0.006). The difference between groups was significant (p=0.003). PMT made from mung beans and catfish significantly improved children’s weight. Study limitations include small sample size, short intervention duration, and reliance on parental reporting. Future studies are recommended to include larger samples, longer interventions, direct observation of consumption, and consider dietary patterns, health status, and variations of local food preparations.